A mixed methods study of the teachers’ self-efficacy views and their ability to improve self-efficacy beliefs during teaching - Şenol Orakcı; Derya Yüreğilli Göksu; Savaş Karagöz (Frontiers in Psychology, 2023)
ObjectiveThe current study has the aim of investigating teachers’ views about their self-efficacy and how they improve their self-efficacy beliefs during teaching practice.MethodsThe study was designed in a mixed methods research design. “Teacher’s Self-Efficacy Scale,” “Personal Information Form” and “Semi-structured Interview Form” were employed in the study. The quantitative data were collected from 379 teachers in public schools in the 2021–2022 academic year, whereas the qualitative data were obtained from the top 10 participants with the highest level of self-efficacy.Results and DiscussionBased on the qualitative and quantitative results of the present study, it was revealed that teachers’ self-efficacy levels were high, and they felt self-efficient in their teaching.The study is of great importance since determining teachers’ opinions about their self-efficacy beliefs and how they improve their self-efficacy beliefs in the solution of the problems they encountered during teaching practice will not only raise awareness of the importance of self-efficacy in teaching profession, but will contribute to further research and qualified teacher training.